Circ_0058792 regulates osteogenic differentiation through miR-181a-5p/Smad7 axis in steroid-induced osteonecrosis of the femoral head. Issue 5 (2nd May 2022) - Han, Ning; Qian, Fei; Niu, Xianping; Chen, Guoting
ABSTRACT: Osteonecrosis of the femoral head (ONFH) caused by steroids is a severe orthopedic disorder resulting from the use of high-dose steroid drugs, characterized by structural changes in the bone, joint dysfunction, and femoral head collapse. CircRNAs and miRNAs have increasingly been suggested to play pivotal roles in osteogenic differentiation and osteogenesis. Significant upregulation of circ_0058792 was observed in patients with steroid-induced ONFH. Bioinformatic analysis showed that circ_0058792 might act as a sponge for miR-181a-5p. This study further investigated the mechanisms underlying the role of circ_0058792 and miR-181a-5p in osteogenic differentiation in methylprednisolone-induced ONFH rats and MC3T3-E1 cells. The results showed a notable decrease in the serum of miR-181a-5p in methylprednisolone-induced ONFH rats. Silencing of circ_0058792 using siRNAs and overexpression of miR-181a-5p significantly increased alkaline phosphatase activity and matrix mineralization capacity. Additionally, markers for osteogenic differentiation were significantly upregulated in miR-181a-5p-transfected cells. However, overexpression of circ_0058792 and the addition of the miR-181a-5p inhibitor reversed this increase. Smad7 was identified to be miR-181a-5p's direct target and circ_0058792 was confirmed to be miR-181a-5p's competing endogenous RNA (ceRNA). Upregulation of miR-181a-5p promotes phosphorylation of Smad2 and Smad3. Furthermore, circ_0058792 and miR-181a-5p had opposing effects on Smad7 expression. Collectively, these findings indicate that circ_0058792 regulates osteogenic differentiation by sponging miR-181a-5p via the TGF-β/Smad7 pathway. These findings elucidated the functions of circ_0058792 and miR-181a-5p in the regulation of steroid-induced ONFH. Our findings also indicated that circ_0058792 and miR-181a-5p are possible diagnostic markers and therapeutic targets for treating steroid-induced ONFH. Graphical abstract: uf0001